Analysis of cost-effectiveness of agricultural yield from vegetable farming - Omar, Mohamad Adam; Omar, Mohamad Nazuhan; A. Rahaman, Zullyadini (2015)

(untitled)
Most developed countries in the world depend heavily on agriculture but scarce attention has been paid to studies on the cost-effectiveness of agricultural yield from vegetable farming, especially by the relevant authority. While the total agricultural yields obtained are high in terms of economic perspective, however the cost of fertilizers and soil loss in agricultural areas are not taken into account. The loss of nutrients from fertilizers and soil in agricultural activities need to be stressed because it can cause significant losses to agricultural producers in term of soil fertility. As such, the objectives of this study were to investigate the agricultural gross revenue earned by the type of crop and current crop price, to estimate the amount of nutrient loss from fertiliser and soil loss by crop type and to analyse the cost-effectiveness of agricultural yield. Four types of vegetables were selected for this study, namely Spinach (Amaranthus oleraceus L.), Red Chili and Chili Padi (Capsicum frutescens L.) and Cucumber (Cucumis sativus L.) planted in an open slope of 5º at a plot size of 1.5m x 2.0m. The rainfall in this study was produced by a rainfall simulator at a pressure of 7 psi that can produce rainfall intensity of 67 mm/hr. From this study, the total amount of vegetables harvested from each plot was 2.96 kg for Spinach, 2.67 kg (Red Chili), 0.51 kg (Chili Padi) and 4.52 kg for Cucumber. In terms of current market value, Spinach yielded RM 10.03, Red Chili RM 53.37, Chili Padi RM 10.20 and Cucumber RM 12.90. The amount of soil loss is 9.43 kg for Spinach, 7.6 kg for Red Chili, 3.94 kg for Chili Padi and 9.86 kg for Cucumber. For the nutrient loss, Spinach yielded 12.58 g, Red Chili (11.51 g), Chili Padi (8.04g) and Cucumber (11.51g). The total cost of nutrient and soil loss is RM 6.33 for Spinach, Red Chili RM 5.12, Chili Padi RM 2.67 and Cucumber RM 9.96 respectively. Hence, the net profit of each vegetable during the study period is RM 3.70 for Spinach, RM 48.25 Red Chili, RM 7.53 Chili Padi and RM 2.94 Cucumber. This study suggested that the cost of nutrient loss from fertilizer and the soil loss should be considered in the determination of current market price of vegetables. In agricultural practice, the farmers should consider the amount of nutrient and soil loss in order to sustain the fertility of the soil from the agricultural activities.